N-219 AIRCRAFT TRAFFIC DISTRIBUTION MODEL BASED ON THE MOVEMENT POTENTIAL OF THE COVERAGE ZONE AT SULTAN SYARIF KASIM II AIRPORT PEKANBARU - Ilma Tsabrilia; Juang Akbardin; Odih Supratman (Journal of Development and Integrated Engineering, 2021)
Pekanbaru Sultan Syarif Kasim II Airport has a limited domestic flight schedule. Based on data from Angkasa Pura II, Pekanbaru Sultan Syarif Kasim II Airport serves flights to 14 domestic destinations. By using a small aircraft type N-129 with a capacity of 19 passengers, it will be able to produce several new routes that are possible to be formed and the aircraft can enter on short runways. The volume of passenger traffic at Sultan Syarif Kasim II Airport Pekanbaru is projected in 2029 to reach 8749856 passenger departures per year and 7515557 passenger arrivals per year. With the N-219 plan aircraft, one main zone and five coverage zones are obtained to distribute passenger movements. In the Origin-Destination Matrix analysis using the Furness and Fratar method, a more constant calculation is the Fratar Method. The number of aircraft needed per day with the Furness Method is at most 8 N-219 aircraft with the Pekanbaru - Palembang route. The maximum number of aircraft needed per day using the Fratar Method is 7 N-219 aircraft with the Pekanbaru - Palembang route and vice versa.